Modaliteti integracije prakse u obrazovanje arhitekata i unapređenje nastavnih planova i programa / Modalities of Practice Integration within the Architects Education and Curricula Improvement - Salihović, Erdin; Burazor, Mladen; Salihbegović, Amira; Islambegović, Vedad (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
The curriculum of the University of Sarajevo Faculty of Architecture (UNSA AF) has evolved from a predominantly theoretical framework and setting imaginary tasks to recognizing and adequately responding to current topics and real social problems. However, the inert institutional character is noticeable, limiting the academic community's timely response to urgent challenges and societal changes. To eliminate the identified shortcomings and improve the education process, the Faculty of Architecture has undertaken several activities in cooperation with partnering institutions in BiH and the EU, resulting in critical self-evaluation and novel guidelines. Previous examples of collaboration with industry illustrate possible ways to improve the quality of education and raise student competencies. The newly designed ERASMUS + project “APLE” (2022) aims to integrate practice and cooperation with the real sector to transfer (applicable) knowledge into the teaching process. New formats of interaction with the real and public sector “ARCHIPRAXIS” are envisaged as a testing ground for implementing various ideas. This paper aims to present the importance and modalities of incorporating the practical component into the process of student education and the actualization of global topics in the local context. It also wants to point out the inertia and shortcomings in the existing academic procedures at different levels, which should be valorized as extracurricular activities. The experience gained, i.e., "lessons learned," should serve all actors involved in the educational process: academia, and industry, to the broader community to create a better framework for acquiring and applying knowledge.